ANALISIS PENAWARAN DAN PERMINTAAN SERTA POTENSI EKSPOR DAGING BABI INDONESIA - KARIYASA, I KETUT; ILHAM, NYAK (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 3, No. 1 Februari 2003, 2012)
Supply and demand analysis model of pork meat in Indonesia, including the capability of its export rate, using national time series data period 1975-1999.This analysis is using econometrical approach with Ordinary Least Squares (OLS) method. The result shows that from supply side, price of meat itself, price of the pork, net import of pork meat, and quantity population of pork influence it. From demand side, influenced by the price of its meat, price of fish, and income. In ten year ahead, the capability of export rate for pork meat will be large enough, and considered to be 48,7% from production. This rate could be reached by improving quality of cattle and meat, making conducive environment for investing and spreading out this cattle business into large area, which support its environment living from many aspects, such as social, cultural, and religion aspect.
Keywords: Supply, Demand, Export fork Meat, OLS